Factors underlying a disproportionate increase in hospital admissions for adrenal insufficiency in women aged 20-29 years - Rushworth, Rosemary Louise; Falhammar, Henrik; Torpy, David J. (Frontiers in Endocrinology, 2023)
Since the year 2000, admissions for adrenal insufficiency (AI) and adrenal crises (AC) have shown a particular increase in young adult females. We examined data on acute non-surgical hospitalisations for AI/AC from New South Wales, Australia, to determine relevant factors that may have contributed to this increase. Data were analysed to ascertain associations between various comorbid psychosocial issues, identified by relevant ICD-10-AM codes in each record, and ACs. From 2005 to 2021. There were 877 admissions for an acute non-surgical illness in this age group. The average admission rate for females [63.5/million/year] was almost twice that for males [34.0/million/year] (p<0.01), as was the average female AC admission rate [14.7/million/year] relative to that in males [6.75/million/year] (p=NS). Infection was present in 41.6% (n=365) of the admissions and Type 1 diabetes mellitus was present in 12.2% (n=107). Overall, psychosocial factors were considered by the senior clinician to have contributed to the illness episode in 22.1% of all admissions and 29.0% of AC admissions. Having one or more psychosocial problems was associated with an AC in females (37.4%, n=49, in those having an AC, p<0.001) but not males. Females with an AC also had a higher mean composite psychosocial, psychiatric and drug/alcohol score [0.47 (0.67)] than females without an AC [0.32 (0.62) p<0.05]. No comparable associations were found in male patients. An increase in the rates of hospitalisations that included a code for at least one psychosocial problem was highly correlated with increases in admission rates for both ACs (r=0.82, p<0.001) and all AI (r=0.98, p<0.001) in females but there was no such relationship in males. This new evidence suggests that psychosocial factors may play an important role in ongoing rates of ACs in treated AI (incidence approximately 6-8 ACs/100PY) particularly in young adult females. In order to minimize AC episodes, all barriers to self-management need exploration on an individual patient basis and with regard to the patient population as a whole.